Platelet satellitism in chronic renal failure: an experimental study - Gupta Vibha; Ahmad Shahbaj; Chandra Harish; Shrivastava Vikas (Society of Diabetic Nephropathy Prevention, 2015)
The phenomenon of platelet satellitism (PS) is characterized by formation of platelet rosettes around polymorphonuclear leukocytes. We present a case of chronic Kidney disease that developed PS after second cycle of dialysis. A group of experiments have been conducted that suggested that contrary to common belief, anticoagulant does not play any role. In view of available literature we suggest that this phenomenon could be related to either or both of the hemodynamic stress and biocompatibility of the dialysis membrane.